The Importance of Bibliometric Studies. The Orinoquia Case (2010)
Astract: The wealth of scientific information generated in recent years combined with new forms of communication, has led the research community to propose the measure, which has given rise to a new discipline of bibliometrics. This uses mathematical and statistical analysis methods that allow obtaining reliable indicators related to quality. Thus, it is possible to obtain information on the number of documents issued by an institution or a country, research groups or individuals with the greatest scientific productivity.